Cor e translucidez de materiais restauradores estéticos - Nogueira, Audrea Dallazem (2012)
Examining the color and translucency of different ceramics and resin-based composites, testing the hypotheses that (1) manufacturer color designation does not match Vita Classical shade guide, (2) methods using spectrophotometers to evaluate translucency reduce the subjectivity from the visual method, and (3) the use of a coupling medium influences the color and translucency values. Specimens of different color were fabricated from composites (Filtek Z350 XT, 4Seasons, Empress Direct, and Esthet-X HD) and ceramics (IPS e.max CAD, IPS Empress CAD, Paradigm C e Cerec Mark II). The translucency was observed visually (MV%) using a standard scale. A spectrophotometer (Vita Easyshade) was used to obtain the CIELab color coordinates and the reflectance value (Y) of all specimens on white and black backgrounds. The translucency parameter (TP) and the contrast ratio (CR) were calculated. Another spectrophotometer (Lambda 20) measured the direct light transmittance (T%) of the specimens. CIELab coordinates were also assessed using the Vita EasyShade spectrophotometer on neutral gray background and used to calculate the ▲E values. All analyses were repeated using a coupling medium (glycerin). The results were statistically analyzed using Anova and Tukey tests (α = 0.01), Student's t test (α = 0.05) and Pearson correlations. There were significant differences in translucency of evaluated materials by all methods, which showed strong correlation, mainly for the ceramic materials. A greater manufacturer color designation to Vita Classical shade guide match was showed for composites than for ceramics. Glycerin significantly changed the mean translucency values and color perception (p<0,01) and increased (about 8%) the correlation between translucency methods